(3GdEYdGe HahGFO YeOI GdCMcGes - (3YeQ Hf Ydj Hf CMeO GdCfUGQj GdTGaYj, SQGL GdOjf, CHh MaU GHf GdfMhj, GdeYQha HGHf Gdedbf, J (B804 (3g` s; (3Jbj GdOjf CHj eMeO YHO GdZfj Hf YHO GdhGMO Hf Ydj Hf SQhQ GdLeGYjdj GdebOSj GdLeGYjdj GdMfHdj,J (B600 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdQVGY s
(3BNQgG (B:s
(3jfJgi HcJGH GdYJb s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs